2012
DOI: 10.1007/s11104-012-1283-7
|View full text |Cite
|
Sign up to set email alerts
|

An Epichloë endophyte affects the competitive ability of Festuca rubra against other grassland species

Abstract: Background and aims: Festuca rubra plants are asymptomatically infected by the systemic fungal endophyte Epichloë festucae and high infection rates have been found in natural grasslands. Our objective was to determine the effect of endophyte infection on the competitive ability of Festuca rubra in binary mixtures against other grassland species. Methods: In two glasshouse experiments, endophyte-infected (E+) and non-infected (E-) plants of two half-sib lines (PEN, RAB) of Festuca rubra were grown in monocultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 50 publications
1
36
0
1
Order By: Relevance
“…In contrast, three genotypic strains of Epichloë lolii (previously Neotyphodium lolii Leuchtmann et al 2014), another asexual fungal endophyte species, infecting perennial ryegrass decreased growth of white clover when grown in mixture, but differences between endophyte strains were not attributed to strain-specific alkaloid profiles (Sutherland et al 1999). Root and leaf extracts of red fescue infected with Epichloë festucae reduced seed germination of both red and white clover (Vázquez-de-Aldana et al 2011), and E. festucae-infected red fescue has also been shown to inhibit red clover biomass production and reduce growth of other legumes when grown in mixture (Vázquez-de-Aldana et al 2013). Furthermore, in tall fescue, Peters and Mohammed Zam (1981) found reduced germination and root growth of red clover and birdsfoot trefoil when subjected to tall fescue extracts of unknown endophyte status, and Springer (1996) later found that extracts from both E-and CTE+ tall fescue reduced red clover germination and root growth.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, three genotypic strains of Epichloë lolii (previously Neotyphodium lolii Leuchtmann et al 2014), another asexual fungal endophyte species, infecting perennial ryegrass decreased growth of white clover when grown in mixture, but differences between endophyte strains were not attributed to strain-specific alkaloid profiles (Sutherland et al 1999). Root and leaf extracts of red fescue infected with Epichloë festucae reduced seed germination of both red and white clover (Vázquez-de-Aldana et al 2011), and E. festucae-infected red fescue has also been shown to inhibit red clover biomass production and reduce growth of other legumes when grown in mixture (Vázquez-de-Aldana et al 2013). Furthermore, in tall fescue, Peters and Mohammed Zam (1981) found reduced germination and root growth of red clover and birdsfoot trefoil when subjected to tall fescue extracts of unknown endophyte status, and Springer (1996) later found that extracts from both E-and CTE+ tall fescue reduced red clover germination and root growth.…”
Section: Introductionmentioning
confidence: 99%
“…() and Vázquez‐de‐Aldana et al. () who found positive effects of endophyte infection on the interspecific competitive ability of host plants. Our results further suggest that endophytes facilitate coexistence between a subordinate plant species ( A .…”
Section: Discussionmentioning
confidence: 97%
“…grandis , which lacks endophytes. So far, few studies have tested the effects of endophyte infection on the competitive ability of native grasses (Brem & Leuchtmann, ; Craig et al., ; Faeth et al., ; Vázquez‐de‐Aldana et al., ). Our results show that endophyte infection can increase the competitive ability of the host plant A. sibiricum , with higher biomass and aggressivity index than the endophyte‐free plants.…”
Section: Discussionmentioning
confidence: 99%
“…Epichloë festucae can have highly variable effects on F. rubra growth and biomass production, ranging from no effect (Zabalgogeazcoa et al 2006) to negative (Vázquez-de-Aldana et al 2012) or positive (Wäli et al 2009) effects. Variation in these effects has been linked to plant genotype and habitat of origin (e.g., Vázquez-de-Aldana et al 2012;Wäli et al 2009). Similar to a previous study (Wäli et al 2009), we found that endophyte-infected plants invested more in root over shoot tissues than uninfected plants (Supplementary text, Supplementary Fig.…”
Section: The Costs and Benefits Of Endophytes To Plantsmentioning
confidence: 99%
“…Specifically, they can alter host resource allocation to increase their own transmission, which sometimes reduces allocation to plant reproduction (Faeth 2009;Gorischek et al 2013;but see Faeth 2010;Rudgers et al 2010). Conversely, the positive effects of endophytes range from increased competitive ability (Vázquez-de-Aldana et al 2012) and allelopathy (Vázquez-de-Aldana et al 2011) to decreased preference and performance of herbivores on infected grasses (Crawford et al 2010). However, these effects on herbivores can depend on herbivore identity (Afkhami and Rudgers 2009) and endophyte reproductive strategy (i.e., sexual or asexual) (Tintjer and Rudgers 2006).…”
Section: Introductionmentioning
confidence: 99%